Constructing Servanthood in Popular Islamic Music: A Semiotic Analysis of Maher Zainâ€™s â€œQalbi Sajadâ€ - Prasetya, Rahima Wandra; Laily Fitriani (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
Arabic religious songs have become an important medium for expressing and transmitting Islamic values; however, their lyrical meanings are often overlooked due to linguistic barriers and listeners’ focus on musical elements rather than textual interpretation. Despite the popularity of Qalbi Sajad, scholarly studies that examine its ideological meaning construction through semiotic analysis remain limited. This study aims to analyze how the concept of servanthood is constructed in the lyrics of Qalbi Sajad through denotative, connotative, and mythological levels of meaning using Roland Barthes’ semiotic framework. Employing a qualitative semiotic approach, this study analyzes selected lyrical expressions as cultural signs operating within a system of signification. The findings reveal that servanthood is represented denotatively through acts of worship such as prostration, calling, supplication, and crying; connotatively through inner devotion, spiritual communication, absolute dependence, and unconditional love; and mythologically through the naturalization of Islamic ideological values such as tauhid, tawakkal, and mahabbah as the existential condition of the servant. By extending Barthes’ concept of myth to contemporary Arabic religious song lyrics, this study contributes to semiotic scholarship and Islamic cultural studies, while also highlighting the pedagogical potential of Arabic religious songs as authentic materials in Arabic language education.